Note to the Spanish pharmacopoeia IX edition: Calcium lactate - García Villanova, R.; Saenz de Buruaga y Lerena, J. (Ars Pharmaceutica (Internet), 1970)
A gravimetric and complexometric technics of evaluation ofr calcium lactate has been revised. We recomanded a complexometric technic, using EDTA and murexide as indicator, in order to include it in the new Spanish Pharmacopeia edition.